RE-INTERPRETATION THE CARDINAL ORIENTATION NOTION IN CHINESE TEMPLES IN BALI - Hendrawan, Freddy; Noreen, Michelle (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2020)
Chinese traditional cardinal orientation is one of the vital concepts in Chinese traditional architecture as it is conveying philosophical and practical meanings, though here, this concept has been altered in Chinese temples in Bali. This article explores the implementation of cardinal orientation notion in Chinese temples in Bali contributing to valuable insight upon how the architectural and cultural identity of Chinese traditional architecture is maintained. The spatial layout data of Chinese temples in Bali’s regencies will be examined to understand how the notion of Chinese traditional cardinal orientation is re-interpreted and applied. It shows that Chinese temples in Bali mostly adopted the Chinese traditional geomancy facing the buildings to the waterways instead of north-south or east-west orientation due to local geographical re-orientation. In addition, these Chinese temple orientations have also been influenced by the site characteristic and the temple’s historical background. This article concluded that the essential notion of cardinal orientation in Chinese traditional temple layouts has been re-interpreted by adopting the local context to maintain its architectural and cultural identities.